Pressure Drop Hysteresis of Hydrodynamic States in Packed Tower for Foaming Systems - Vijay Sodhi; Renu Gupta (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2011)
An experimental investigation was carried out to determine the effects of gas and liquid flow velocities and surface tension on the two-phase phase pressure drop a in a downflow trickle bed reactor. Water and non- Newtonian foaming solutions were employed as liquid phase. More than 240 experimental points for the trickle flow (GCF) and foaming pulsing flow (PF/FPF) regime were obtained for present study. Hydrodynamic characteristics involving two-phase pressure drop significantly influenced by gas and liquid flow rates. For 15 and 30 ppm air-aqueous surfactant solutions, two-phase pressure drop increases with higher liquid and gas flow velocities in trickle flow and foaming/pulsing flow regimes. With decrease in surface tension i.e. for 45 and 60 ppm air-aqueous surfactant systems, two-phase pressure drop increases very sharply during change in regime transition at significantly low liquid and gas velocities. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)